PRAGMATIC FUNCTIONS OF LOANWORDS IN RUSSIAN AND CHINESE - Pak, R.; Orazakynkyzy , F. (Journal of Oriental Studies, 2025)
The following study compares the processes of borrowing foreign words and concepts in the Russian and Chinese languages. Particular attention is paid to the analysis of the features of English loanwords since the lexicon of social networks and mass media is dynamic and much more often replenished with new concepts from the English language, which is currently a universal means of international communication. The study’s relevance is due to the increased interest in understanding the processes of change in modern languages ​​of different systems under the influence of globalization, a comparison of the processes of borrowing in languages, taking into account the national specifics of the language. The study provides a detailed review of scientific sources and literature, describes the research methods, and also provides the results of a comparative analysis of modern Russian and Chinese speech and highlights the main layer of borrowed vocabulary. The discussion section proves that the main functions of borrowing foreign words coincide in both Chinese and Russian due to the strong position of the English language in the period of globalization as a means of international communication. Keywords: loanwords, Russian language, Chinese language, English loanwords, comparative study.